CircXRCC5, as a Potential Novel Biomarker, Promotes Glioma Progression via the miR-490-3p/XRCC5/CLC3 Competing Endogenous RNA Network. (1st July 2022) - Chen, Ping; Nie, Zhen-Yu; Liu, Xiao-Fei; Zhou, Min; Liu, Xuan-Xin; Wang, Bing
Graphical abstract: Schematic graph of circXRCC5 in glioma development. In glioma cells, circXRCC5 binds to miR-490-3p, assembling with Argonaute family protein Ago2 into the effector complex called RNA-induced silencing complex (RISC), which mediates the inhibition of sequence-specific target gene XRCC5 silencing. The upregulated XRCC5 directly interacts with CLC3 promoter to positively modulate the transcriptional activity of CLC3, as a result, promoting glioma progression. Highlights: CircXRCC5 is upregulated in glioma tissues and cell lines. Knockdown of circXRCC5 suppresses cell proliferation, migration and invasion in glioma cells. The effects of circXRCC5 are mediated by sponging miR-490-3p. XRCC5 is directly targeted by miR-490-3p and is a transcriptional activator of CLC3. CircXRCC5/miR-490-3p/CLC3 axis is involved in the progression of glioma. Abstract: Circular RNAs (circRNAs), forming a covalently closed loop, are identified as a special subgroup of non-coding RNAs. Herein, we investigated the function and underlying mechanism of circXRCC5, generated from the XRCC5 gene, in glioma progression. Bioinformatics analysis was employed to determine the genomic information of circXRCC5 derived from XRCC5 pre-mRNA. Quantitative real-time PCR was conducted to examine the expression of circXRCC5 in glioma tissues and cells. Stable knockdown of circXRCC5 in U87 and U251 cells was established to assess its' biological functions. Cell Counting Kit-8, EdU incorporation, flow cytometry and transwell assay were performed to evaluate cell proliferation, apoptosis, migration and invasion, respectively. The circRNA–miRNA–mRNA regulatory network was verified using luciferase reporter assay and RNA immunoprecipitation. The samples were subjected to CHIP to ascertain the transcriptional regulation of XRCC5 at the promoter region of CLC3. Up-regulation of circXRCC5 was observed in glioma tissues and cell lines, and indicated poor prognosis of glioma patients. Knockdown of circXRCC5 suppressed cell proliferation, migration and invasion, while facilitated apoptosis. Mechanistically, circXRCC5 acted as a molecular sponge for miR-490-3p in a sequence-specific manner. There was a reciprocal negative feedback between circXRCC5 and miR-490-3p in an Argonaute2-dependent manner. Moreover, circXRCC5 acted as a sponge of miR-490-3p to regulate the expression of downstream target gene XRCC5, thus activating the transcription of CLC3, which fostered the progression of glioma. Collectively, circXRCC5 promoted glioma progression via the miR-490-3p/XRCC5/CLC3 ceRNA network, providing a novel prognostic biomarker and a prospective target for glioma treatment.